Interdecadal Variability of Extensive and Persistent Extreme Cold Events in China and Their Atmospheric Circulation Causes - Ziqi LIU; Yao LU; Yan LI (Gaoyuan qixiang)
The interdecadal characteristics and atmospheric circulation causes of the extensive and persistent extreme cold events （EPECE） in China are analyzed in this paper based on NCEP/NCAR and the dataset CN05.1 of daily mean temperature from 1961 to 2018.The results show that there is an overall fluctuating decreasing trend characteristic of the occurrence days of EPECE from 1961 to 2018， but the trend turns around 1995， and the occurrence days of the events before 1995 have a significant decreasing trend， and the events are mainly of the countrywide type； after 1995， the trend becomes increasing， and the main types are the northwestern/Jiangnan type and mid-eastern type.By analyzing the atmospheric circulation field with the Siberia high index， blocking high index， and potential vorticity （PV） anomaly characteristics， the atmospheric circulation causes of the northwestern/Jiangnan type and mid-eastern type of events after 1995 were comparatively studied.The results further showed that the strong Eurasian polar vortex became weak during the EPECEs from 1961 to 1995， the frequency of blocking high in Ural was low at 21.8%， the maximum anomalies of the Siberia high index was 8.9 hPa， and the anomalous low PV circulation in Ural was strong with a northeast-southwest axis， which was a typical anticyclonic Rossby wave breaking， it allowed cold air to move southward to affect most parts of the country.During the EPECEs from 1996 to 2018， the Eurasian polar vortex was continuously replenished and maintained in the process of weakening， the frequency of Ural blocking high reached 34.6% and the range was east-north， the anomalies of Siberia high reached 11.5 hPa， and the high vortex air located in the Baikal region was relatively weak， and the anomalously low PV circulation was able to move eastward and northward from Ural to north of Lake Baikal， thus affecting the Ural blocking high can be extended to central Eurasia， making it possible for cold air to reach more southern regions and maintain it for a long time when it affected China during 1996 -2018.